New species and records of Oukuriella Epler, 1986 from the Neotropical region (Diptera: Chironomidae) - Bellodi, Carolina Ferraz; Fusari, Lívia Maria; Roque, Fabio De Oliveira (Zootaxa, 2016)
Two new species of Oukuriella, O. angelomachadoi sp. nov. (Holotype male deposited in MZUSP: BRAZIL, Paraná State) and O. plumaterata sp. nov. (Holotype male deposited in MZUSP: BRAZIL, São Paulo State), and the immatures stages of O. sublettei are described and figured. The larvae of O. sublettei were collected from submerged woods in low-order streams in the Atlantic Forest. In addition new records of several described species, including the first records of Oukuriella from Mexico and Bolivia are given.